Deprescribing antipsychotics: a guide for clinicians. (13th August 2018) - Gupta, Swapnil; Cahill, John Daniel; Miller, Rebecca
SUMMARY: Polypharmacy and the risks of long term use of antipsychotic medications point toward the need for identifying practices for deprescribing in psychiatry. The following article gives a brief overview of key points around deprescribing antipsychotic medications in psychiatry, including identifying risks and benefits, considerations around timing, and steps involved. LEARNING OBJECTIVES: Be able to define the concept of deprescribing as it relates to antipsychotic medications Know how to perform a risk–benefit analysis for a patient on antipsychotic medication Be able to identify the key steps involved in deprescribing antipsychotic medications DECLARATION OF INTEREST: None.